Agronomic performance of Safflower genotypes (Carthamus tinctorius L.) under different soil bulk density levels in the Oxisol of the Cerrado - Paludo, Juliana Terezinha Sasso; Bonfim-Silva, Edna Maria; da Silva, Tonny José Araújo; de Freitas Sousa, Helon Hébano; Zanotto, Maurício Dutra [UNESP]; Fenner, William (Southern Cross Publishing, 2018)
As intensive farm development can cause changes in soil structure, it is crucial to study cultivars that can adapt to these changes, along with the climatic conditions of the Cerrado of Mato Grosso. The objective of this study is to assess the effects of soil bulk density (weight of soil in a given volume) on the agronomic performance of the safflower genotypes (Carthamus tinctorius L.). The experiment was conducted at the Federal University of Mato Grosso in a greenhouse. A completely randomized design in factorial scheme with four replications was selected. The treatments comprised of five soil bulk density levels (1.0, 1.2, 1.4, 1.6 and 1.8 Mg m-3) and ten safflower genotypes (PI 237538, PI 248385, PI 250196, PI 301049, PI 305173, PI 305205, PI 306596, PI 306603, PI 560202 and PI 613366). The following evaluations were done after completion of the experiments: total shoot dry mass, upper ring root dry mass, intermediate and lower total root dry mass. The data were subjected to the analysis of variance and the means were categorized by the Scott-Knott test at the 5% level of probability. The genotypes and soil bulk density influenced the components in isolation ways. The shoot dry mass production was impaired from the bulk density of 1.10 Mg m-3. For the root dry mass, the limit was 1.04 Mg m-3. In general, from the soil density of 1.20 Mg m-3 the growth and development of safflower genotypes were influenced negatively. The increase in soil density reduced the total root dry mass up to 71.11%.
Keywords: Carthamus tinctorius L.; Oleaginous plants; Plant physiology; Root development; Soil compaction